Weakened Zones in Wood – Based Composite Beams and Their Strengthening by CFRP: Experimental, Theoretical, and Numerical Analysis - KULA, Krzysztof; SOCHA, Tomasz; DENISIEWICZ, Arkadiusz (Engineering Transactions, 2019)
This paper looks at the mechanical behaviour of wood-based beams. Laboratory tests of an I-beam show a considerable decrease of capacity in the weakened zones, e.g., at the connection between two pieces of pine wood used as a flange. We propose strengthening of the zones using fibre composite tapes based on CFRP. This article demonstrates the way for protection of the I-beam with defects in the bottom flange against the loss of load-carrying capacity. The required anchor length is determined by an analytical method formulated in the paper. The numerical results are presented. The full adhesion between CRFP and wood is assumed in the numerical simulations.